Effect of irrigation regimes and sources of nitrogen on the growth, yield, economics and soil nitrogen of cauliFlower (Brassica oleracea var botrytis subvar cauliflora) production - IDNANI, L K; THUAN, N T Q (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted during 2003-04 and 2004-05 to study the effect of irrigation regimes and nitrogen through different organic sources and urea on yield. water use parameters and soil nitrogen of cauliflower (Brassica oleracea var botritys subvar cauliflora).The irrigation at 30 mm CPE recorded significantly the highest plant height (43.0 cin), number of leavesiplant (18.3), leaf area index (2.6), stalk length (9.2 cm), dry matter production (105.7 glplant), days to final maturity(l05.5), total biomass yield(54.4 tonnes/ha), marketable yield (1 8.2 tonnes/ha) and available soil nitrogen (259.4 kgiha) and the highest net return (Rs 49 447) and benefit:cost ratio (4.10) as compared to 20 and 40 rnnl CPE during both the years. While irrigation at 20 mmCPE recorded significantly the highest harvest index (0.38 1) during both the years, respectively. Application of 50 kg Ntha through urea + 5 tonnes/ha farmyard manure resulted in significantly the highest plant height (43.5 cm), number of leaves per plant (19.0), leaf area index (2.7) dry matter production (I 18.2 gl plant), total biomass production (50.9 tonnesiha), marketable yield (1 8.3 tonnes/ha), total soil nitrogen (0.047 %) and the highest net return (Rs 48 880) and benefit:cost ratio (3.78) during both the years. An application of 75 kg N/ha (urea) recorded significantly the highest stalk length (9.2 cm). Similarly, application of 25 kg N/ha through urea t Azotobacter + 5 tonnes/ha farmyard manure recorded significantly the highest harvest index (0.400) during both the years, whereas applicationof 50 kg N/ha through urea+ Azotobacter + 5 tonnes/ha farmyard manure, recorded significantly the highest days to final maturity (105.7) and available soil nitrogen (268.1 kg/ha) during both the years respectively.